How the Turn to Practice may Contribute to Working Life Studies - Gherardi, Silvia (Nordic Journal of Working Life Studies, 2015)
Working life studies and practice-based studies have a common interest for work, and how work is accomplished in situated working conditions. The turn to practice may contribute to renew the study of work. The main concern of a practice-based approach to working practices is to understand the logic of the situation and the performance of action as practical knowledge, which connects working with organizing and knowing with practicing. The article will first illustrate the basic assumptions of an approach to working practices based on a post-humanist practice theory and second it will focus on a specific contribution from it. I shall argue that a practice approach to innovation as a continuous process contributes to a better understanding of how working practices change or persist. In fact, the study of work in situation is not only descriptive in its purpose, but it is also intended to yield practical outcomes for empowering practitioners in their attachment to practicing.